Vitamin B12 Deficiency in the South of Jordan: A Possible Geographical Correlation: Vitamin B12 in Jordan - Al Zoubi, Mazhar Salim (Progress in Nutrition, 2022)
Vitamin B12 deficiency has been associated with certain serious disorders such as megaloblastic anemia as well as cardiovascular, neurological, and psychological disorders. Vitamin B12 deficiency is a worldwide health concern and a severe health problem in certain developing countries. In the current study, we aimed to evaluate the situation of vitamin B12 and estimate the prevalence of vitamin B12 deficiency in southern Jordan. The study population included 281 participants from Aqaba city: 71.2% females and 28.8% males with a mean age of 30.01±13.5. The results showed that the average vitamin B12 level was 277.34±103.70 pg/mL. The study population showed that 69 (24.6%) participants had a vitamin B12 deficiency. The current findings showed a lower frequency of vitamin B12 deficiency in the studied population compared to the rest of Jordan, especially in the north. The females reported a significantly higher frequency of vitamin B12 deficiency (29.0%) compared to the male group (13.6%). In addition, the CBC parameters showed a significant association between the level of vitamin B12 and Hb, RBC, PCV, and platelet count with a p-value = 0.044, <0.001, 0.021, 0.025, respectively. On the other hand, the results showed a lack of association between the vitamin B12 level and MCV and age group. In conclusion, the current study supports our previous findings regarding the correlation between geographical locations and the deficiency of vitamin B12. These findings can be attributed to the lifestyle and nutrient situation in Aqaba city which relies more on seafood. Moreover, other factors such as genetic predisposition can be excluded as an association factor. Therefore, more studies are required to evaluate vitamin B12 levels in Jordan at a higher scale that will include genetic analysis as well as food habits.